Full-field strain measurement using optimal path search method with error control. (May 2022) - Chen, J.P.; Tao, W.J.; Huan, S.; Nie, Z.C.
Highlights: An optimal path search method (OPSM) with error control for full-field strain measurement of material is proposed. The OPSM is implemented by optimizing the algorithm of the traditional digital image correlation method. The validity of the OPSM is verified by two numerical model experiments and a quasi-static compression experiment of 3D printed cellular structure. The OPSM method improves the calculation accuracy of the strain field in the boundary, hole, and zone with an abrupt change in displacement. Abstract: Digital image correlation (DIC) is one of the main means of optical measurement of the strain field. However, there has been little discussion on the calculation errors at positions with abrupt change. This study seeks to address how to reduce the full-field strain calculation errors and improve the strain accuracy. An optimal path search method (OPSM) with error control for a full-field strain solution is proposed by optimizing the algorithm of the traditional DIC method, using the material displacement field with abrupt change. The strain calculation considering the calculation zone boundary, hole, and shock wave front is discussed. A comparison of the results using the proposed method with the theoretical results shows that this method can effectively obtain full-field strain information, especially at positions with abrupt change in displacement. The application of OPSM to the cellular structure in a quasi-static compression experiment again verifies the validity. This method not only is comparable with the original method in the noise suppression effect but also ensures the approximation of the results to the true values in the displacement zone with abrupt change.